2022
DOI: 10.1371/journal.pone.0269823
|View full text |Cite
|
Sign up to set email alerts
|

Squalene in oil-based adjuvant improves the immunogenicity of SARS-CoV-2 RBD and confirms safety in animal models

Abstract: COVID-19 pandemic has accelerated the development of vaccines against its etiologic agent, SARS-CoV-2. However, the emergence of new variants of the virus lead to the generation of new alternatives to improve the current sub-unit vaccines in development. In the present report, the immunogenicity of the Spike RBD of SARS-CoV-2 formulated with an oil-in-water emulsion and a water-in-oil emulsion with squalene was evaluated in mice and hamsters. The RBD protein was expressed in insect cells and purified by chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Moreover, this formulation was able to stimulate neutralizing antibodies in hamsters. Results confirmed that SQ base emulsion was safe, as demonstrated by the histopathological analysis in lungs, liver, and kidney 35 . Due to the effective properties of SQ, Solomadin et al, applied SQ in NARUVAX-C19 vaccine as an emulsion adjuvant and obtained robust broadly neutralizing humoral and T cell IFN-γ responses 36 .…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, this formulation was able to stimulate neutralizing antibodies in hamsters. Results confirmed that SQ base emulsion was safe, as demonstrated by the histopathological analysis in lungs, liver, and kidney 35 . Due to the effective properties of SQ, Solomadin et al, applied SQ in NARUVAX-C19 vaccine as an emulsion adjuvant and obtained robust broadly neutralizing humoral and T cell IFN-γ responses 36 .…”
Section: Discussionsupporting
confidence: 64%
“…Compound known to have effects on immune system as immunostimulants is squalene [6]. Squalene is known for its anticancer properties [7], cardiovascular benefits [8], and its role as a COVID-19 vaccine adjuvant [6]. The demand for squalene in the pharmaceutical industry is projected to reach 184 million USD by 2025 (9).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effectiveness of current vaccines, the constant evolution of the virus poses a significant threat to public health [ 4 , 5 ]. Adjuvants have been identified as a promising strategy to improve vaccine efficacy by promoting, improving, and maintaining the immune response to the vaccine antigen [ [6] , [7] , [8] , [9] ]. Previous experiences with influenza and malaria vaccines have demonstrated the importance of adjuvants during pandemics and their potential to accelerate vaccine development [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%